«Русский» и «американский» периоды творчества Айн Рэнд - Иванникова, Е.С. (Культура народов Причерноморья, 2014)
В данной статье рассматриваются «русский» и «американский» периоды творчества Айн
Рэнд. Научная новизна определяется мало изученностью творчества данной писательницы. Русская по
происхождению, она эмигрирует в США через несколько лет после революции. Айн Рэнд в своих
произведениях выступает не в роли бесстрастного репортера, она дает эмоциональную оценку
происходящему. Самые известные ее романы предостерегают от проблем возможного будущего
человечества. В работе прослеживается путь становления и развития литературного таланта Айн
Рэнд. У даній статті розглядаються «російський» і «американський» періоди творчості Айн Ренд.
Наукова новизна визначається мало вивченістю творчості даної письменниці. Російська за
походженням, вона емігрує до США через кілька років після революції. Айн Ренд в своїх творах виступає
не в ролі безпристрасного репортера, вона дає емоційну оцінку тому що відбувається. Найзнаменитіші
її романи застерігають від проблем можливого майбутнього людства. У роботі простежується шлях
становлення і розвитку літературного таланту Айн Ренд. The present study deals with the philosophical concept of the bilingual writer A. Rand. The relevance
of the research due to the ever-increasing interest of bilingual and bicultural writer in the context of
globalization. This article discusses the "Russian" and "American" periods of the Ayn Rand. The scientific
novelty is determined about unexplored creativity of this writer. She emigrated to the United States a few years
after the revolution. Her most famous novels warns against possible future problems of mankind. She is a
creator of one of the most influential philosophical concepts of our time. She is for the development of individual
rights for the sake of a human being not for the sake of the state. The main purpose is the embodiment of the
state, dictatorship and is against a human being as it deprives a personality of the right to choose. The
philosophical paradigm of Ayn Rand's ideology of collectivism considers the substrate as the suppression of the
individual by the state. Personality against the rules, prevents the development of thought and creative abilities
are the most important significance of individuality. The path of formation and development of the literary talent
of Ayn Rand is presented. The most famous novels warn from fatal problems of possible future mankind.